HUBUNGAN ANTARA KEPUASAN KERJA DAN KOMITMEN ORGANISASI: STUDI KASUS DI HITAY INVESTMENT HOLDING - Christian Kuswibowo (Universitas Mercu Buana, 2017)
Is there any relationship between Job Satisfaction and Organizational Commitment?Today, one of the most fundamental issues of managers is improving job satisfaction ofthe employee and organizational commitment. It is impossible to get efficiency from anemployee who is not satisfied with his job and has a low organizational commitment.Therefore, these two concepts must be well understood to keep up the activities oforganizations in an effective way. Normally, enterprises should meet the expectations andneeds of the employees. Only in this way, the enterprises can motivate their employees.And employees will develop a commitment within the frame work of organizationalconditions in which they are motivated and satisfied and also by increasing theirperformance in this direction, they will make efforts in line with the objectives of theorganization itself. For this reason, which is vital in sustaining the business, the employeesmust do their best to increase job satisfaction and organizational commitment.In thisstudy, the effects of Job Satisfaction and Organizational Commitment were diagnosed.The research was carried out in Hitay Investment Holding in İstanbul. In order todetermine the job satisfaction, Manual for the Minnesota Satisfaction Questionnaire byWeiss, Dawis, England, Lofquist (1967) was used. the organizational commitment, Meyerand Allen (1997) The ‘Three-component model of organizational commitment’ was used.In the analysis process of the acquired data, an appropriate statistics programme has beenused with the demographical information of 89 employees have been collected.Correlation Coeffıcients and Regression Analysis has been applied in order to measure therelationship between job satisfaction and organizational commitment.Finally, it comes to aresult that there is a significant relationship between job satisfaction and organizationalcommitment. In the end of this thesis, some suggestions have been proposed to themanagers in order to increase the job satisfaction and organizational commitment ofemployees.